The Himalayan Aspects of Change and A Brief Survey of Nepali Historiography - Lal, J. S. (Himalayan Review, 2011)
Not necessary. Key words: Himalayan aspects; Nepali historiography The Himalayan Review Vol. 14, 1982 Page: 52-64 Uploaded Date: April 10, 2011